Strategi Supervisi Pendidikan Dalam Meningkatkan Performa Guru - Ziyadul Ifdhal Ghazali; Ahmad Rofiqi Tanzil; Saylatur Robab (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The implementation of supervision in educational institutions is an inevitability. Its purpose is to ensure that instructional practices within these institutions are carried out in accordance with established standards. This study aims to explore the implementation of an educational supervision program as an effort by MA Darul Ulum Banyuanyar to enhance teachers’ performance in the teaching and learning process. The research employs a qualitative approach, utilizing descriptive analytical techniques to comprehensively examine the supervision program. This includes its planning, implementation, evaluation, and the strategies used to address challenges encountered. Data were collected through observation, interviews, and verification of supervision-related documents at MA Darul Ulum Banyuanyar. The findings indicate that the supervision program has been conducted periodically by the school principal and relevant stakeholders. The process begins with verifying the readiness and completeness of teachers’ instructional documents, followed by regular monitoring of the implementation of teaching programs. Additionally, discussion and consultation forums are facilitated to promote teachers’ professionalism and improve their performance in instructional practices.